Representasi Psikologi Sastra pada Film Penyalin Cahaya Karya Wregas Bhanuteja - Azzahra, Rahmani; Solihati, Nani (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2024)
In this study the aims to describe the literary psychological representation of the main character's personality, namely Suryani, in the film "Penyalin Cahaya" by Wregas Bhanuteja, using Sigmund Freud's Psychoanalysis theory, namely Id, Ego, and Superego. This study employs a descriptive qualitative method by describing the analysis results that have been found. The data and data sources used include scene images, monologues, and dialogues in the film "Penyalin Cahaya," with the data source being the film "Penyalin Cahaya" available on Netflix. Data collection techniques in this study involve observation, listening, note-taking, and categorization based on data grids. The findings of this research show that the ego personality structure yields balanced results with the id personality aspect. Suryani is depicted as a resilient figure in seeking evidence for the events that occur to her. However, in terms of the id personality aspect, Suryani engages in pleasures that have negative consequences, thus the superego aspect plays a role in providing Suryani with values external to her personality.